2016
DOI: 10.3390/biology5020014
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Crohn’s Disease-Associated Isolates from Other Pathogenic Escherichia coli by Fimbrial Adhesion under Shear Force

Abstract: Shear force exerted on uropathogenic Escherichia coli adhering to surfaces makes type-1 fimbriae stretch out like springs to catch on to mannosidic receptors. This mechanism is initiated by a disruption of the quaternary interactions between the lectin and the pilin of the two-domain FimH adhesin and transduces allosterically to the mannose-binding pocket of FimH to increase its affinity. Mannose-specific adhesion of 14 E. coli pathovars was measured under flow, using surface plasmon resonance detection on fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 66 publications
(98 reference statements)
1
13
0
Order By: Relevance
“…SPR experiments with natural variants of FimH (e.g., aa. 158; Table 1 ) found in different E. coli strains corroborate the importance of the linker loop in the shear-dependent conformational change [ 22 , 46 , 47 ]. The analysis of sMD simulations combined with experimental data highlighted that below a force of about 60 pN, the unbinding of the mannose is mainly observed from the LA state (with a rate of 6 s −1 [ 61 ].…”
Section: The Molecular Binding Mechanism Of Small Mannosidic Composupporting
confidence: 61%
See 1 more Smart Citation
“…SPR experiments with natural variants of FimH (e.g., aa. 158; Table 1 ) found in different E. coli strains corroborate the importance of the linker loop in the shear-dependent conformational change [ 22 , 46 , 47 ]. The analysis of sMD simulations combined with experimental data highlighted that below a force of about 60 pN, the unbinding of the mannose is mainly observed from the LA state (with a rate of 6 s −1 [ 61 ].…”
Section: The Molecular Binding Mechanism Of Small Mannosidic Composupporting
confidence: 61%
“…Independent of the used sMD approach the interdomain linker loop extended under the applied force. In line with the observed importance of the linker, SPR experiments highlight that natural variants of FimH with different amino acids in the position 158 (located in the linker loop region, see Figure 1 A) show different responses to stress [ 22 , 46 , 47 ]: the adhesion strength of the uropathogenic UTI89 E. coli strain with a threonine at position 158 of FimH shows an optimum at higher shear, whereas in strains (AIEC7082 and LF82) carrying an alanine or a proline respectively at aa. position 158, bacterial binding is less or not enhanced with increasing fluid shear.…”
Section: The Molecular Binding Mechanism Of Small Mannosidic Compomentioning
confidence: 72%
“…Binding of anti-adhesives at the clamp loop holding Ile13 where large shear-force induced conformational changes occur, with the interplay of aglycon stacking with either the Ile13 or the Tyr48 side chain, is a mechanism as yet little explored in drug discovery of FimH antagonists of E. coli adhesion [ 42 ]. These novel structural insights, namely that ortho -biphenyl substituents on mannose can sample a binding interface on the FimH adhesin, notably one that is directly involved in the regulation of FimH affinity of pathogenic E coli under shear force, opens new perspectives for non-antibiotic therapies and anti-adhesive design [ 39 , 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These variants are often single point, non-synonymous amino acid substitutions found in the lectin domain but not affecting the mannose-binding pocket directly. While adaptive mutations identified in our study were also found in the lectin domain of the protein, only position 87 (G87C) has been previously described in pathoadaptive variants 28,44,45,48 and described as a mutational hotspot with amino acid changes to arginine, alanine, serine and cysteine 28 . The G87S and G87C variants are the only mutants that display moderate increases in mannose-binding, but still display catch-bond properties under flow conditions 28 .…”
Section: Discussionmentioning
confidence: 45%